TYPES OF FATAL TRAUMA EXAMINED IN THE FORENSIC DEPARTMENT OF DR. MOEWARDI HOSPITAL - Suwandono, Adji; Atmoko, Wahyu Dwi (STMIK Widya Cipta Dharma, 2024)
Trauma means violence against living tissue which can have physical or psychological effects, where trauma is the third largest cause of death and disability worldwide. Trauma can be classifed into sharp trauma and blunt trauma. This study aims to describe the types of trauma that cause death and the sosciodemographic characteristics of trauma victims at the Forensix Department of Dr. Moewardi Hospital in 2017-2021. This study uses a descriptive observational method. The data comes from the Visum et Repertum file in the Forensic Department of Dr. Moewardi Hospital in 2017-2021. The research sample totaled 193 cases using the total sampling technique. The data analysis technique used is descriptive analysis. The results of the study were the most common type of trauma causing death was blunt trauma with a percentage of 88.6%, the most common sex was male at 81.35%, the most common age level was found in adults (26-65 years) at 57%, the type of forensic examination the most frequently carried out were external examinations of 77.72%, and most of the crime scenes occurred outdoors at 91.2%. The type of trauma that causes the most deaths in the Forensic Department of Dr. Moewardi Hospitl in 2017-2021 was blunt trauma, with the most cases being male, the most ages at the adult, the most types of forensic examinations external examinations, and the most crime scenes outside buildings.